The Lusophone World in French Political and Internet Discourse - Ana Zwitter Vitez (Verba Hispanica)
The paper aimed to examine the terms related to the concept of Lusophony in the French political and internet discourse to better understand the role of the Lusophone world in French-speaking society. We conducted a grammatical and contextual analysis of the words Portugal, Brésil, and lusophonie (and their adjectives) as they are used in the Europarl corpus and the FrTenTen corpora. The results show interesting differences between the two discourse genres. In political discourse, the examined words are related mostly to discussions about the economy, environmental issues, and food exports. On the other hand, in online discourse the analysed terms are most frequently applied to the topic of football, but also to discussions about colonization and beauty treatments (like Brazilian hair straightening). Utilizing the analysis presented in this study we could not detect the topic of culture, which is an unexpected result with regard to the global importance that Lusophone culture has in the field of music (e.g. fado and bossa nova), dance (e.g. samba and capoeira), and literature (e.g. Fernando Pessoa and José Saramago).